2020
DOI: 10.3389/fnhum.2020.00219
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and Vulnerability: Neurodevelopment of Very Preterm Children at Four Years of Age

Abstract: Children born very preterm (VPT) are at high-risk for altered brain development and impaired neurodevelopmental outcomes but are not well-studied before school-age. We investigated 64 four-year-olds: 37 VPT children [<32 weeks gestational age [GA]; 22 males; mean GA: 28.8 weeks ± 1.6], 25 full-term (FT) children (12 males), plus two VPT cases with ventriculomegaly and exceptionally resilient outcomes. All children underwent high-resolution structural magnetic resonance imaging and developmental assessments. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Further, SA was not a robust predictor of GA in the replication sample. These findings are perhaps not surprising given the inconsistent findings related to SA in the prior literature ( Skranes et al, 2013 ; Grunewaldt et al, 2014 ; Sølsnes et al, 2015 ; Zhang et al, 2015 ; Mürner-Lavanchy et al, 2018 ; Hasler et al, 2020 ; Sripada et al, 2018 ; Young et al, 2020 ). Considering the pattern of effects for SA and CT, we see that in both there are reductions in children with PTB in temporoparietal regions, but estimates diverge in several other regions.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Further, SA was not a robust predictor of GA in the replication sample. These findings are perhaps not surprising given the inconsistent findings related to SA in the prior literature ( Skranes et al, 2013 ; Grunewaldt et al, 2014 ; Sølsnes et al, 2015 ; Zhang et al, 2015 ; Mürner-Lavanchy et al, 2018 ; Hasler et al, 2020 ; Sripada et al, 2018 ; Young et al, 2020 ). Considering the pattern of effects for SA and CT, we see that in both there are reductions in children with PTB in temporoparietal regions, but estimates diverge in several other regions.…”
Section: Discussionmentioning
confidence: 58%
“…Reduced SA has also been found in anterior temporal ( Sølsnes et al, 2015 ), inferior frontal ( Sølsnes et al, 2015 ), and ventral visual ( Sripada et al, 2018 ; Hasler et al, 2020 ) regions. However, some studies have reported no group differences in SA ( Mürner-Lavanchy et al, 2018 ; Young et al, 2020 ).…”
Section: Introductionmentioning
confidence: 98%
“…Differences in adjusted temporal lobe volumes could indicate altered brain organization in infants with CAH, with a potential association with intrauterine exposure to excess androgens. Notably, unaffected male infants have been found to exhibit higher adjusted temporal volumes compared to unaffected female infants [30], and increases in adjusted temporal lobe volumes are known to be related to poor cognitive outcomes later in life [31]. It would be worthwhile to study further the relationship between early brain differences and later developmental changes in children with CAH.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the incredible advancement of neonatal intensive care, preterm born neonates are at greater risk of developing neurodevelopmental deficits and psychiatric disorders later in life than full-term born neonates (Ortinau & Neil, 2015;Volpe, 2009a). The common believe is that these developmental insults may deleteriously have an impact on microscale (van Tilborg et al, 2018) and macroscale neonatal brain growth trajectories around term equivalent age (Kelly et al, 2016;Monson et al, 2016) and during childhood (de Kieviet et al, 2012;Lax et al, 2013;Ment et al, 2009;Nosarti et al, 2014;Taylor et al, 2011;Young et al, 2020). Even in the absence of macroscopic brain damage, decreases in brain volumes in preterm born children are predictors for general cognitive function impairments later in life (Cheong et al, 2013;Hadaya & Nosarti, 2020;Kelly et al, 2016;Keunen et al, 2016;Nosarti et al, 2008;Taylor et al, 2011;Thompson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%